Characterization of untreated and alkali treated natural fibers extracted from the stem of Catharanthus roseus. (29th May 2019) - Vinod, A; Vijay, R; Singaravelu, D Lenin; Sanjay, M R; Siengchin, Suchart; Moure, M M
Abstract: The present investigation deals with the study of untreated and alkali treated natural fibers extracted from the stem of Catharanthus roseus . The physical, chemical, crystallinity, mechanical, wettability, thermal, and surface characteristics were analyzed for untreated and alkali treated Catharanthus roseus fibers (CRFs). The results showed that chemical treatment removed excess amorphous contents such as hemicellulose, lignin and wax contents thereby there was an enhancement in tensile strength, crystalline index, and surface roughness. The char residue upon thermogravimetric analysis got increased from 25.2% to 39.6% for untreated and alkali treated CRFs respectively. The alkali treated CRF showed lesser contact angle which proved its improved wettability in the liquid phase. Thus the improvement in the characteristics of the alkali treated CRF can make it useful for developing lightweight polymer composites.